After the anthropause: Lockdown lessons for more‐than‐human geographies. Issue 1 (27th January 2021) - Searle, Adam; Turnbull, Jonathon; Lorimer, Jamie
Abstract : The drastic reductions in human activities and mobilities associated with quarantines implemented to curb the spread of SARS‐CoV‐2 was recently described as "the anthropause" by Christian Rutz and colleagues. Field scientists argue that the anthropause is a once‐in‐a‐lifetime opportunity for observation and data collection in a world devoid of anthropogenic disturbances, notably those from extractive industries and travel. In this commentary, we unpack the anthropause as a spatio‐temporal event, attending to its geographies, histories, and genealogies. There are multiple precursors of anthropause events which have locally altered human impacts on the environment. We document the ways in which the COVID‐19 anthropause has brought into focus human–animal relations through an analysis of the practices of scientists, publics, and nonhuman animals themselves. Following Arundhati Roy, we conclude by advancing an understanding of the pandemic as a "portal" rather than a pause, identifying lockdown lessons from the anthropause for a post‐pandemic new normality. Abstract : The drastic reductions in human activities and mobilities associated with quarantines implemented to curb the spread of SARS‐CoV‐2 has been described as "the anthropause." In this commentary, we unpack the anthropause as a spatio‐temporal event, attending to its geographies, histories, and genealogies. Following Arundhati Roy, we conclude by advancing an understanding of the pandemic as a "portal" rather than a pause, identifying lockdown lessons from the anthropause for a post‐pandemic new normality.